DIGITAL BUSINESS navigating the digital landscape and thriving in the digital economy. - SEUWOU, PATRICE (ROUTLEDGE, 2026)
This comprehensive guide explores the fundamentals of digital business, from understanding digital business models to leveraging emerging technologies and trends.This work begins by examining the rise of digital business and the disruption it caused within traditional industries. Chapters then delve into key topics such as building a digital business strategy, designing a strong online presence, e-commerce, digital marketing, data analytics, cybersecurity and more. Written in a clear and accessible style, the author provides real-world examples to illustrate how successful companies have leveraged digital technologies to drive growth and achieve their business goals. Each chapter features case studies, learning objectives and key discussion questions to augment student learning.This new text is recommended reading for undergraduate and postgraduate students of Digital Business, Digital Marketing, and Business Analytics. It will also be valuable reading for reflective practitioners in the industry.This book is accompanied by online resources including PowerPoint slides, an instructor's manual, a test bank of questions, and worksheets for each chapter, providing instructors with the necessary tools to keep their courses up to date, engaging, and effective in preparing students for the ever-changing digital business landscape.